Examining the Relationship Between Mental Toughness and Anxiety Levels of Professional Volleyball Players - Erdoğan, Ramadan; Kavuran, Korhan; Şimşek, Ayşegül (Health Nexus, 2025)
The main objective of this research is to reveal the relationship between anxiety levels and mental toughness among professional volleyball players and to determine how these constructs differ according to demographic variables. The study group consisted of 139 voluntary athletes (86 female. 53 male) who are licensed and actively competing in volleyball in the Eastern Anatolia Region. The data collection tool used in the study consisted of two parts: the first part was the “Personal Information Form” used to identify the demographic characteristics of the athletes; the second part included the “Sport Anxiety Scale” to measure the anxiety levels of the athletes and the “Sports Mental Toughness Questionnaire” to assess their mental toughness levels. The data were analyzed using the SPSS statistical software. and the level of significance was set at p